Strategi Pemenuhan Komoditas Tanaman Pangan Melalui Pendekatan Model Dinamis: Food Crop Commodity Fulfilment Strategies Through a Dynamic Modelling Approach - Obadja Fenetiruma; Michael A. Baransano; Zulkifli Kilian (Jurnal Agritechno, 2026)
Teluk Bintuni is one of the insecure food regions in Indonesia. In 2023, the total production of food crops in Teluk Bintuni is below of food requirement. This research aims to develop a strategy to fulfill the food crop requirement in Teluk Bintuni through a dynamic model approach using the Vensim 10.0.0 educational version software. Generally, this research consists of four main stages, i.e., data inventory, dynamic model design, data analysis, and recommendations. The research shows that food demand in Teluk Bintuni can be fulfilled through the optimization of land that has been provided by the government. Other solutions are increasing the Cropping Index (CI) from 2 times to 3 times and using superior varieties that have higher productivity.